Glycolic acid-g-chitosan-gold nanoflower nanocomposite scaffolds for drug delivery and tissue engineering - Kumari, Sangeeta; Singh, Raj Pal (International Journal of Biological Macromolecules, 2012)
This paper reports a simple novel method for the synthesis of flower like gold nanoparticle (three dimensional branched nanoparticle) with >30 tips, under controlled temperature condition. Formation of flower like Au nanoparticle was confirmed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Next step of this paper reveals the potential use of novel hybrids of chitosan-g-glycolic acid and gold nanoflower (AuNF) in controlled drug delivery and tissue engineering applications. The drug loaded novel nanohybrid scaffold is prepared by freeze drying of grafted polymer solution. Grafting of glycolic acid to the chitosan and incorporation of drug were evaluated by Fourier transform infrared spectroscopy (FTIR). The nanohybrid scaffolds were found to be stable towards the pH of the medium. The cell viability study shows that prepared nanohybrid scaffolds are biocompatible. Gold nanoflowers were found to control the drug release rate in the buffer solution (pH 7.4). Therefore, for the glycolic acid grafted chitosan based system, gold nanoflowers are the viable additive for drug delivery. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Chitosan; Drug delivery system; Glycolic acid grafting; Gold nanoflower; Nanocomposite

Glycolic acid-g-chitosan-Pt-Fe3O4 nanoparticles nanohybrid scaffold for tissue engineering and drug delivery - Kumari, Sangeeta; Singh, Raj Pal (International Journal of Biological Macromolecules, 2012)
This work presents the potential use of novel nanohybrid based on chitosan-g-glycolic acid and Pt-Fe3O4 composite nanoparticles in drug delivery and tissue engineering applications. The Pt-Fe3O4 hybrid nanoparticles are prepared by thermal decomposition of H2PtCl6 center dot 6H(2)O at high temperature. The prepared nanoparticles were characterized by transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and physical property measurement system (PPMS). Next step of this paper reveals the potential use of novel hybrids of chitosan-g-glycolic acid and Pt-Fe3O4 hybrid nanoparticles in controlled drug delivery applications. The drug loaded nanohybrid scaffold is prepared by freeze drying of grafted polymer solution. Drug loading and grafting of chitosan was characterized by Fourier transform infrared spectroscopy (FTIR). The cell proliferation also shows that the prepared nanohybrids are biocompatible. The nanohybrid was found to be stable regardless of pH of the medium. Therefore, Pt-Fe3O4 hybrid nanoparticles are viable additive for sustained drug delivery and it could be applied in the field of biomedical. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Cell viability; Chitosan; drug delivery; Glycolic acid grafting; Pt-Fe3O4 hybrid nanoparticle

Characterization of a novel nanocomposite film based on functionalized chitosan-Pt-Fe3O4 hybrid nanoparticles - Kumari, Sangeeta; Singh, Raj Pal; Chavan, Nayaku N.; Sahi, Shivendra V.; Sharma, Nilesh (Nanomaterials, 2021)
The development of organic-inorganic hybrids or nanocomposite films is increasingly becoming attractive in light of their emerging applications. This research focuses on the formation of a unique nanocomposite film with enhanced elasticity suitable for many biomedical applications. The physical property measurement system and transmission electron microscopy were used to analyze Pt-Fe3O4 hybrid nanoparticles. These nanohybrids exhibited magnetic effects. They were further exploited to prepare the nanocomposite films in conjunction with a chitosan-g-glycolic acid organic fraction. The nanocomposite films were then examined using standard techniques: thermogravimetric analysis, X-ray diffraction, Fourier transform infrared spectroscopy, and atomic force microscopy. Tensile strength testing demonstrated a significantly greater elastic strength of these nanocomposite films than pure chitosan films. The water absorption behavior of the nanocomposites was evaluated by measuring swelling degree. These nanocomposites were observed to have substantially improved physical properties. Such novel nanocomposites can be extended to various biomedical applications, which include drug delivery and tissue engineering.
Keywords: Chitosan; nanocomposite films; Pt-Fe3O4 hybrid nanoparticles; tensile strength testing; Thermogravimetric analysis